Revitalisasi Profesi Partonun Melalui Interaksi Langsung dengan Pembeli Kain Ulos di Pematang Siantar (Studi Etnoarkeologi Pendekatan Simbiosis) - Defri Elias Simatupang (Balai Arkeologi Sumatera Utara, 2011)
AbstractUlos is a traditional cloth that being worth now. There are three elements which related of ulos, there are weaver, distributor, and buyer. Trough the interaction happened, its time to learn about their symbiosis and offer better solution to reincrease ulos and partonun worth.